ANALISIS ASUPAN ZAT GIZI BATITA BERDASARKAN TINGKAT PENDIDIKAN, STATUS BEKERJA DAN PENGETAHUAN IBU - chabibah, Nur; Khanifah, Milatun; Kristiyanti, Rini (Poltekkes Kemenkes Semarang, 2021)
Background: Acute malnutrition could increase mortality and morbidity indirectly in infants and toddlers. The family socio-economic characteristics including the maternal education, nutritional knowledge, and family income, are related to the incidence of stunting.Objective: To determine the relationship between maternal education, working status and knowledge on dietary intake among toddlers under 3 years old.Methods: A correlative analytic study with cross-sectional design. The populations were mothers with toddlers under 3 years old. Sample size were 70 mothers which obtained with the cluster random sampling technique. Data collection were used questionnaire and calculated with 2005 Nutria survey and 14 levels.Results: There were no significant relationship between education level and working status on dietary intake of children under 3 years old (OR: 0,88; ᵖ-value: 0,855; CI: 0,136-4,136) and (OR: 1,29 ᵖ-value: 0,674; CI: 0.298-4.987). However, there were significant relationship between maternal knowledge and dietary intake of children under 3 years, especially related with energy and protein intake (OR: 2,14 ᵖ-value: 0,043; CI: 1,043-17,045). Conclusions: Maternal knowledge level are related to dietary intake among children under 3 years old, relared with energy and protein intake.